Bhutan’s Unique Development Paradigm and the Green School Model of Restorative Learning - S. Powdyel, Thakur (Futures of Education, Culture and Nature - Learning to Become, 2024)
This essay, penned by former Minister of Education Thakur S. Powdyel, illuminates the contrast between Bhutan's Gross National Happiness (GNH) framework and the traditional Gross Domestic Product (GDP) metric. Unlike GDP, which fixates on economic output, GNH takes a holistic approach to development, encompassing environmental, social, cultural, intellectual, and spiritual dimensions. The Green School initiative, a living embodiment of GNH, is not just an educational model, but a comprehensive life-enriching experience. It aims to cultivate well-rounded individuals through the Sherig Mandala, which integrates eight essential elements: Nature, Society, Culture, Intellect, Academics, Aesthetics, Spirituality, and Ethics. The essay underscores how the Green School initiative, guided by the principles of GNH, fosters a comprehensive educational experience that contributes to sustainable development and the well-being of both individuals and society.